Seagrasses of Costa Rica: from the mighty Caribbean to the dynamic meadows of the Eastern Tropical Pacific - Samper Villarreal, Jimena (2018)
Seagrass meadows are declining worldwide, mostly attributed to anthropogenic disturbances. Understanding the dynamics of these meadows is urgent in order to establish adequate management and conservation strategies. Here, we analyzed the current knowledge on the seagrass meadows in the Caribbean and Pacific coasts of Costa Rica, Central America. Current knowledge was based on literature searches, herbarium collections, informal interviews, and personal observations. We report a total of five genera and seven species for Costa Rica: Thalassia testudinum, Syringodium filiforme, Halophila decipiens, Halophila baillonis, Halodule wrightii, Halodule beaudettei, and Ruppia maritima. Six species are reported for the Caribbean, and four species for the Pacific. Thalassia testudinum, S. filiforme, and H. decipiens have only been reported for the Caribbean. Halodule beaudettei has only been reported for the Pacific coast. Halophila baillonis, H. wrightii and R. maritima have been reported for both coasts. Seagrasses were found at a total of 31 locations in Costa Rica, most from the Pacific coast; 16 of which are reported here for the first time. Seagrass meadows from both coasts are vastly different. Along the Caribbean coast, meadows are often dominated by the robust T. testudinum, they are extensive and stable, persisting for decades. In contrast, the meadows along the Pacific coast are more dynamic and are dominated by pioneer and smaller ephemeral species, such as H. baillonis and H. beaudettei. The number of studies on Costa Rican seagrasses is scarce but has been increasing over time, and mostly concern taxonomic reports and basic descriptions of the dynamics of T. testudinum meadows from the Caribbean. Research, conservation and management efforts on Costa Rican seagrass meadows would benefit from continued monitoring and research on associated fauna and flora, incorporating ecosystem resilience and services.